THE DIGITAL HUMANITIES: A Primer for Scholars and Students - Dr. Nia Kurniasih, M.Hum. (Fakultas Seni Rupa dan Desain ITB, 2021)
The Digital Humanities: A Primer for Students and Scholars is written by Eileen Gardiner and Ronald G. Musto as a resource for undergraduate and postgraduate students working in the field of the digital humanities. Overall, the well-structured book discusses how technological developments have presented scholars and students with new grounds to explore the methodology, pedagogy, and public history aspects of digital history. It tries to respond to such questions as whether the Digital Humanities (DH) is a field of study or a methodology, if it is a social science, a humanistic, or a technological discipline, or whether it is the study of the interaction between computing and humanities.